Evaluation of carrot (Daucus carota L.) varieties for growth and yield as affected by NPSB fertilizer rates in Gondar district, Ethiopia - Mulugeta, Abebaw; Asrat, Fentahun; Asres, Derajew; Mebrat, Shiferaw (Frontiers in Plant Science, 2025)
Carrot (Daucus carota L.) is one of the most important root crops grown worldwide and in Ethiopia. However, its production and productivity are low due to a lack of improved varieties and unbalanced fertilizer rates, among other factors. The field experiment was, therefore, conducted to determine the performance of carrot varieties through blended fertilizer rates at Gondar district for a consecutive period of two years. The treatment consisted of six rates of blended NPSB (Nitrogen, phosphorus, sulfur and Boron) fertilizer (0, 40.6, 81.3, 122, 162.3, and 203.4 kg ha-1) and two carrot varieties (Haramay-I and Nantes), which were laid out in a randomized complete block design with three replications. The main effect of blended NPSB received in 162.3 kg ha-1 obtained the highest root diameter (3.38 cm), root length (20.93 cm), and root volume (110.60 mm). The main effect of the year was also the maximum number of leaves (10.3), root diameter (2.96 cm), root length (20.09 cm), and root volume (89.20 mm) recorded from the 2021 planting year. On the other hand, in the interaction of variety and NPSB, the highest root fresh weight (134.48 g plant-1) was obtained from the Haramaya-I variety and the application of 162.3 NPSB kg ha-1, while the lowest (57.13 g plant-1) was recorded by the Nantes variety with control. The highest dry matter (13.67%), marketable (50.77 t ha-1) and total (55.32 t ha-1) root yields were recorded from the interaction of 162.3 kg NPSB ha-1 and Haramaya-I variety. Therefore, the planting season and varietal selection should be considered in the carrot production area.